ผลของการจัดกิจกรรมการศึกษานอกระบบโรงเรียนที่มีต่อการคิดวิจารณญาณของเยาวชนในศูนย์เยาวชน - อังคณา ทัศนเมธิน (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purposes of this study were: 1) to study the youths critical thinking level in youth centers 2) to develop non-formal education activity plans on critical thinking of youths in youth centers. 3) to compare the result of non-formal education activities on critical thinking of youths in youth centers 4) to study the participants’ satisfaction towards non-formal education activities on critical thinking of youths in youth centers. The subjects were youths age between 15 to 25 years old in youth centers. The research instruments were activity plans, critical thinking test , a knowledge test , an attitude test, behavior test on critical thinking and satisfaction of the non - formal education activities on critical thinking of youths in youth centers . The research finding were as follows: 1. Mean scores in critical thinking level of youths in youth centers were the lowest level 2. The results from developing the non-formal activity plans on critical thinking of youths in youth centers relevant to the objective of this study to enhance critical thinking of youths. The non-formal activities on critical thinking of youths in youth centers consisted of learning period, learning activities, objective, contents, activity process, media and learning evaluation. 3. 1) The scores of the experimental group s critical thinking level was high and higher than the prior experimentation with statistical significance at level of .05. 2) The scores of the knowledge of the critical thinking after the experimentation increased higher with statistical significance at level of .05. 3) The scores of critical thinking behavior after the experimentation increased higher with statistical significance at level of .05 4) The scores of critical attitude after the experimentation increased higher with statistical significance at level of .05 4. The experimental group scored the satisfaction of the non-formal education activities on critical thinking of youths in youth centers in hight level.